Trinity Growing Globally 2010-2019 - Hussey, Juliette (Trinity College Dublin, the University of Dublin. Office of the Vice-President for Global Relations, 2019)
Introduction: The start of the new academic year: Trinity welcomes over 4,600 international students - including over 2,800 from outside the European Union – and in the year will see more than 800 undergraduates leaving on exchanges, research placements or clinical placements abroad. The incoming international students are introduced to the Global Room and its student ambassadors and encouraged to join societies and help with organising Thanksgiving, Hanukkah, Chinese New Year, Holi and other campus festivals. Meanwhile, round the world, students on the Dual BA programme commence their studies and will spend time at both Trinity and Columbia University in New York; students from Thapar University in Patiala, India continue to articulate into Trinity’s engineering and computer science programmes, a hundred students enter the joint degree programme in physiotherapy in Singapore, we have students joining from Beijing Foreign Studies University and Minzu University of China, and Science Gallery London opens in King’s College London as the first in Global Science Gallery Network, pioneered in Trinity. In short, this last academic year continues Trinity’s growth in global connectivity and campus diversity. This is the new normal. But it’s of recent vintage - just eight years ago in 2010, there were fewer than 1,200 students coming to Trinity from outside the EU and a very limited number of undergraduates going on exchanges beyond the EU, and the programmes supporting these cohorts were not yet in place. Between 2010 and 2018, a revolution occurred in global relations in Trinity. In terms of opening up Trinity to the world and the world to Trinity, we are living a period of rapid change in the 427-year history of the university. How did it happen?
Global Relations Overview 2010-2019
Keywords: Global relations; International students; Student exchanges; Dual BA programme; Global relations strategy; Global partnerships; Research; Trinity College Dublin; Trinity College (Dublin, Ireland). Office of the Vice-President for Global Relations